Partial hepatectomy in a calf with an omphalocele: Case report - Lucas, F. A. [UNESP]; Panelli, E. M. [UNESP]; Nardin Neto, E. [UNESP]; Kandrotas, A. L. [UNESP]; Mastrocinque, S.; Lataro, R. A.; Oliveira, G. G.S. (FapUNIFESP (SciELO), 2016)
An omphalocele is a defect in the closure of the abdominal wall during the embryonic stage, preventing the return of some abdominal organs to the cavity. In stillborn animals, the involvement of the liver in the omphalocele has been reported. The aim of the present study is to report the success of a partial liver resection in a female bovine at two days of age which presented an omphalocele at birth. Surgical intervention was indicated to reduce and suture the abdominal wall. During the surgical procedure, the presence of hard, reddish tissue was noted inside the sac covered by the amniotic membrane, with characteristics consistent with hepatic parenchyma. Due to the impossibility of reducing the contents added to the suggestion of tissue infection, we elected to perform a partial resection. The histopathological examination confirmed that the resected tissue was of the hepatic parenchyma. Antibiotic and systemic anti-inflammatory therapies were performed post-surgery. Fifteen days after surgery, infection was detected at the surgical site in addition to abdominal wound dehiscence; surgical reintervention was performed. On physical examination, carried out 4 months after the second operation, the heifer presented normal development for the species. In conclusion, omphalocele may contain liver. Ectopic liver is an extremely rare condition. Surgical treatment in the presented case focused on umbilicus with exploration of the abdominal cavity appeared to be sufficient.
Keywords: Cattle; Liver resection; Omphalocele